Laser Pulse Effects on Plasma-Sprayed and Bulk Tungsten - Roberto Montanari; Ekaterina Pakhomova; Roberto Pizzoferrato; Maria Richetta; Alessandra Varone (Metals, 2017)
Tungsten (W) is considered a promising plasma-facing material for protecting the divertor of the ITER (International Thermonuclear Experimental Reactor). The effects on W of transient thermal loads of high energy occurring in a tokamak under operative conditions have been simulated through a single laser pulse delivered by an Nd:YAG laser. Bulk and plasma-sprayed (PS) samples have been submitted to tests and successively examined via SEM (scanning electron microscopy) observations. In both types of materials, the laser pulse induces similar effects: (i) a crater forms in the spot central area; (ii) all around the area, the ejection and the movement of molten metal give rise to a ridge; (iii) in a more external area, the surface shows plates with jagged boundaries and cracks induced by thermal stresses; (iv) the pores present in the original material become preferred ablation sites. However, the affected surface area in PS samples is larger and asymmetric if compared to that of bulk material. Such a difference has been explained by considering how microstructural characteristics influence heat propagation from the irradiated spot, and it was found that grain size and shape play a decisive role.